Inflammation laryngeal changes in common cold children - E. P. Selkova; E. Yu. Radtsig; N. V. Ermilova (Журнал инфектологии)
This article is dedicated to the connection between laryngealinflammatory pathology and influenza/common cold.The purpose is to study the frequency of different form of laryngitis in children with common cold/ influenza, influenced of carried laryngitis within common cold on laryngeal structures and also the effectiveness of preventive measures against acute respiratory infections.Material and methods are the results of the examination (including laryngeal endoscopy) and analysis of medical files of 3169 patients and also the data of the annual report of one Moscow semi-clinic.Results. Inflammation laryngeal pathology was revealed in 152 (4,79%) cases, in 129 (84,9%) – non-obstructive. 91 patient (59,8%) belonged to category “frequently and often sick”. The recurrent episodes were seen in patients with both forms of laryngitis. Different laryngeal pathology (laryngitis, vocal nodules) was seen after common cold treatment with 43,5% obstructive and 18,63% non-obstructive laryngitis patient as well as dysphonia in 3-14% getting worse with the following common cold episodes. The preventative measures carried among patients with laryngitis allowed to decrease spreading of this pathology notwithstanding the fact of annual growth of common cold in children.Conclusion. Thus taking to account the high circulation of respiratory viruses the absence of specific preventative measures and the especial role of viruses in development all forms of laryngitis it is recommended to include special drugs in preventative techniques of laryngitis prophylactics. Different methods of non-specific prophylactic are effective in decreasing the amount of common cold episodes, decrease the frequency and severity all forms of laryngitis in children and also tend to stabilize/normalize the voice quality in different laryngeal pathology children.